Not Too Far to Help: Residential Mobility, Global Identity, and Donations to Distant Beneficiaries - Wang, Yajin; Kirmani, Amna; Li, Xiaolin (Journal of Consumer Research, 2021)
Abstract Extant research shows that consumers are more likely to donate to close than distant others, making donations to geographically distant beneficiaries a challenge. This article introduces residential mobility as a novel variable that can lead to increased donations toward distant beneficiaries. This article proposes that residential mobility (vs. stability) leads consumers to have a stronger global identity, whereby they see themselves as world citizens. This global identity results in higher donations to distant beneficiaries. A multi-method approach provides evidence for this prediction. An analysis of a national panel dataset demonstrates that high residential mobility is correlated with donations to distant beneficiaries. Lab experiments, including one with real monetary donations, replicate these effects using both actual moving experience and a residential mobility mindset.